Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ccd.29911
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants in patients with atrial fibrillation and bioprosthetic valve replacement: A meta‐analysis

Abstract: Objectives This systematic review and meta‐analysis compares direct oral anticoagulants (DOACs) versus vitamin K antagonists (VKAs) in patients with atrial fibrillation and bioprosthetic valve replacement or repair (BVR). Background The optimal anticoagulation therapy for patients with atrial fibrillation and a history of bioprosthetic valve replacement or repair (BVR) is not well understood. Methods We performed a systematic literature review to identify clinical studies that compared anticoagulation therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Several studies suggest a preference for NOACs over VKAs among AF patients undergoing surgical BHV replacement [7,54,57,[63][64][65]; however, most of them [48,49,54,55,57,[62][63][64][65] included patients with concomitant antiplatelet therapy leading to several biases both for thromboembolic and bleeding outcomes. Three recent metanalyses [67][68][69] support the use of NOACs over VKAs in AF patients with BHVs, however, the large heterogeneity of the study populations (especially for age and comorbidities) and the inclusion of different valve surgeries make it difficult to generalize the results [67]. Few data support the early use of NOACs even in the first three months [14, ; however, the number of patients randomized in the first 3 months after the procedure is too small to draw definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest a preference for NOACs over VKAs among AF patients undergoing surgical BHV replacement [7,54,57,[63][64][65]; however, most of them [48,49,54,55,57,[62][63][64][65] included patients with concomitant antiplatelet therapy leading to several biases both for thromboembolic and bleeding outcomes. Three recent metanalyses [67][68][69] support the use of NOACs over VKAs in AF patients with BHVs, however, the large heterogeneity of the study populations (especially for age and comorbidities) and the inclusion of different valve surgeries make it difficult to generalize the results [67]. Few data support the early use of NOACs even in the first three months [14, ; however, the number of patients randomized in the first 3 months after the procedure is too small to draw definitive conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the effectiveness and safety of DOACs compared with VKAs in AF patients with BPHV have been explored in several studies (33)(34)(35)(36)(37) as shown in Supplementary Table 5. A prior systematic review by Kheiri et.…”
Section: Discussionmentioning
confidence: 99%
“…Cardoso et al also performed a meta-analysis by including 2 post-hoc analyses of RCTs and two RCTs, suggesting that DOACs were associated with a reduced incidence of SSE and major bleeding as compared with warfarin in AF patients with BPHV (34). In addition to RCTs, the meta-analyses by Adhikari et al, Lacy et al, and Yokoyama et al included a different number of observational studies (33,36,37). To our knowledge, this study is the largest to assess evidence in separate meta-analyses of RCTs (n = 4) and observational studies (n = 7) for DOACs compared with VKAs in AF patients with BPHV.…”
Section: Discussionmentioning
confidence: 99%